IMPLEMENTASI PENDIDIKAN KEAKSARAAN BERBASIS BAHASA IBU DALAM MENINGKATKAN KEBERAKSARAAN: Studi pada Masyarakat Desa Tumbang Masukih Kalimantan Tengah - Affandi, Muhamad (Jurnal Empowerment, 2024)
Literacy is not just about the ability to read and write, but also about how these activities are related to social, cultural, and power structures in society. Some types of literacy have a stronger influence because they are promoted by powerful institutions. However, in various rural areas, especially in remote areas such as Tumbang Masukih Village, Central Kalimantan, the challenges in increasing literacy are still very large. One of the causes is the existence of language barriers, especially for people who use their mother tongue as their daily language. This research aims to examine how the implementation of mother tongue-based literacy education in Tumbang Masukih Village can increase the literacy level of the community. This research was carried out using a qualitative approach using phenomenological methods. Furthermore, the choice of this method focuses on an intensive study of the process of implementing mother-based literacy education learning, especially regarding learning services and techniques in an effort to empower and increase community literacy. From the results of this research, it can be concluded that mother tongue-based literacy education is very effective in improving literacy among the people of Tumbang Masukih Village. Theoretically, these findings support the arguments put forward by various language education experts who state that learning using their mother tongue allows students to understand basic literacy concepts more easily. The process of internalizing knowledge occurs more quickly when the language used is a language that is familiar to students.